The Transport Stability of Flotation Metal Ore Concentrates which are Liable to Liquefaction - Popek, M. (Scientific Journal of Gdynia Maritime University, 2017)
Safety of maritime transport of fine-grained materials, e.g. metal ore concentratesdepends on the ability to control the properties of these cargoes. The dynamic situation,caused by vibration and pressure of layers of cargo during sea transport, makes it change itsphysical properties, porosity, bulk density, degree of compaction and mechanical properties,for example shear strength. The new properties of the cargo result in that there is a risk of itsmovement, as a consequence of the phenomenon of the liquefaction. In the present studywere analysed and evaluated parameters that determine the ability to liquefaction of flotationmetal ore concentrates characterized by different way of sourcing, chemical composition andfragmentation.